PERANCANGAN SISTEM INFORMASI PELAYANAN PUBLIK MENGGUNAKAN FRAMEWORK LARAVEL & MYSQL DI KECAMATAN COBLONG KOTA BANDUNG - R. Adriana Eka Prayudha; Dwi Robiul Rochmawati (INFOKOM (Informatika & Komputer), 2018)
This research aimed to deeply discover how the service staff work systematic in Coblong District Bandung Office.The method that been used in this research is with conducting observation in the place that used for research, doing interviews and conducting literature review. Currently, work system in Coblong District Bandung Office only partially computerized. Conventional method are still used especially for recording E-KTP (Identity Card) and Kartu Keluarga (Family Card) applicant, and also for archiving Legalisir (Document Certifying), Pindah Datang (Coming Civilian) and Pindah Keluar (Departure Civilian). Therefore, a new Information System needed for supporting all the service staff so they can work effectively and efficient. The information system design concept that been used are object oriented approach with UML (Unified Modelling Language) Modelling and implemented with the web application that created with Laravel Framework above the PHP programming language architecture. Whilst, the software development method that been used is waterfall and using MySQL Database.The given by suggestions: 1) Improving the service quality like upgrading the facility and utilize the computerization method so they can giving a better value for society. 2). Needs a system development which are expected to deal with the problems in Coblong District Bandung Office.